Talent in hospitality entrepreneurship: A conceptualization and research agenda. Issue 10 (27th June 2019) - Muskat, Birgit; Lockstone-Binney, Leonie; Ong, Faith; Andresen, Maike
Abstract : Purpose: The purpose of this paper is to develop an integrative conceptual framework of the "talented hospitality entrepreneur". In doing so, the authors address the current lack of understanding of talent at the individual entrepreneurial level and the lack of integration between the talent and entrepreneurship literatures and specifically consider the hospitality context. Design/methodology/approach: This conceptual paper systematically synthesizes the extant literature and links key concepts within talent management, entrepreneurship, hospitality and human resource management to develop a model of the talented hospitality entrepreneur. Findings: Seven propositions emerge from the literature synthesis, and the integrative conceptual model is developed to define the individual antecedents of the talented hospitality entrepreneur and their outcomes for success. Originality/value: To date, understanding of the individual level of talent has been neglected in the management literature. The quandary is that the extant literature on talent has focused on the management of talent at an organizational level, while the entrepreneurship literature has concentrated on spatial macro-level effects. Further, the notion of talent in hospitality literature remains underexplored. Adopting an inclusive view of talent, the authors offer a new integrative framework explaining the constituencies of talent for hospitality entrepreneurs and an associated research agenda.